Shortest Path Routing Using Heuristic Search - Alaiwan, Ahmed Omran A. (2006)
Shortest Path problems are inevitable in road network applications such as city emergency handling and drive guiding system, in where the optimal routing have to be found. To achieve the best path, there are many algorithms which are more or less effective, depending on the particular case. Efficiency depends not only on the time needed for calculation, but also on the reliability of the result. A* algorithm is able to return the best path (if it exists) between two nodes, according to accessibility/ orientation and, of course, cost of arcs. In this project A* algorithm was used, to suggest shortest path model between two selected points to find the fastest and shortest route on Malaysia map. This prototype then guides the users according to their interest and work.